1994
DOI: 10.1083/jcb.124.1.195
|View full text |Cite
|
Sign up to set email alerts
|

Deletions in the cytoplasmic domain of platelet-endothelial cell adhesion molecule-1 (PECAM-1, CD31) result in changes in ligand binding properties

Abstract: Abstract. Platelet/endothelial cell adhesion molecule-1 (PECAM-1, CD31) is a member of the immunoglobulin superfamily present on platelets, endothelial cells, and leukocytes that may function as a vascular cell adhesion molecule. The purpose of this study was to examine the role of the cytoplasmic domain in PECAM-1 function. To accomplish this, wild-type and mutated forms of PECAM-1 cDNA were transfected into murine fibroblasts and the functional characteristics of the cells analyzed. Wild-type PECAM-1 localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

5
82
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(87 citation statements)
references
References 38 publications
5
82
0
Order By: Relevance
“…Previous experiments showed that full-length huPECAM-1 promoted heterophilic aggregation in transfected L-cells in a divalent cation-dependent, heparin-sensitive manner (Albelda et al, 1991;Muller et al, 1992;DeLisser et al, 1993). In contrast, mutants of huPECAM-1 with partially truncated cytoplasmic domains mediated aggregation that was quite different in that it was homophilic, divalent cation-independent, and heparin-insensitive (DeLisser et al, 1994a). These findings raised the possibility that naturally occurring alternatively spliced forms of PECAM-1 might also function differently (Baldwin et al, 1994).…”
mentioning
confidence: 73%
“…Previous experiments showed that full-length huPECAM-1 promoted heterophilic aggregation in transfected L-cells in a divalent cation-dependent, heparin-sensitive manner (Albelda et al, 1991;Muller et al, 1992;DeLisser et al, 1993). In contrast, mutants of huPECAM-1 with partially truncated cytoplasmic domains mediated aggregation that was quite different in that it was homophilic, divalent cation-independent, and heparin-insensitive (DeLisser et al, 1994a). These findings raised the possibility that naturally occurring alternatively spliced forms of PECAM-1 might also function differently (Baldwin et al, 1994).…”
mentioning
confidence: 73%
“…Recent studies on PECAM-1 (platelet endothelial cell adhesion molecule-1) give credence to this suggestion (62)(63)(64): PECAM-1 is a member of the Ig superfamily and is responsible for contacts between leukocytes or platelets with the surface of endothelial cells. Indeed, the last 10 amino acids of Bgp1, surrounding Tyr-515, demonstrate striking homology to a region of 18 amino acids within PECAM-1, particularly those centered around Tyr-686 (Bgp1, SSPRATETVYSEVKKK; PECAM-1, LGTRATETVYSEIRKVDP).…”
Section: Discussionmentioning
confidence: 96%
“…The cytoplasmic domain of adhesion molecules can control their function (52)(53)(54)(55)(56)(57). RBL-2H3 cells bind to fibronectin through integrin receptors resulting in cell spreading and a redistribution of the granules to the periphery of the cells (30,58).…”
Section: Discussionmentioning
confidence: 99%